A Note on the Jointed Wood Poles for Overhead Power and Telecommunication Lines - Rajput, S. S.; Jain, J. D. (Indian Forester, 1980)
Although jointed wood poles are quite often used for overhead power and telecommunication lines specially in hilly and rural areas, only wire bound lap type of joint is commonly adopted. As tests data on other types of jointed poles described in concerned Indian Standard Specification, IS : 6056-1970 is not available, the same has been collected and presented in this paper. It is found that Z-type of lap joint is comparable to wire bound lap joint. While other types of joints taken in the study have come out to be inferrior to these two types of joints.